Insecticide Application Practices Among Lowland and Highland Cruciferous Vegetable Farmers and Their Relationship Upon Plutella Xylostella L. Resistance Development - Chia, Meei Kee (2010)
This study aimed to evaluate the insecticides resistance development of diamondback moth (DBM), Plutella xylostella L. in relation to insecticide application practices. A study was initiated with a survey to assess the current insecticides application practices for controlling DBM in the highland and lowland areas in Malaysia. Survey data were analyzed with SPSS statistical software using Independent-samples T-test and Pearson correlation where appropriate. The survey showed complete reliance on insecticide mixtures to control DBM. A total of 11 and 14 active ingredients of insecticides were found to be commonly used in the lowland and highland respectively. The percentage of highland farmers used indoxacarb, spinosad, pyridalyl and fipronil was higher than lowland farmers, while lowland farmers recorded higher usage of chlorfenapyr than highland farmers. Besides that, a comparative usage for emamectin benzoate was reported, with slight greater use in the lowland (53%) than highland (41%). Highland farmers were found to apply significantly higher spray volume at 3.8-fold greater than lowland farmers (t = 7.361; P<0.05). Majority of insecticides were applied at tank concentrations below recommended doses. Highland farmers were found to apply significantly lower doses of emamectin benzoate compared to lowland farmers.